Areas of employment of the titular ethnic groups of Russia (cases of Tuvans, Bashkirs, Kalmyks, Buryats, Khakass, Yakuts and Dagestanis) - Sirazetdinova, Milyausha F. (The New Research of Tuva, 2025)
The article provides a review of Russian scholarly works addressing the spheres of employment of titular ethnic groups in Russia’s national republics, published from 2000 to the present. The distribution of publications by type, academic centers (authorial affiliations), and year is demonstrated, and developmental stages of thematically focused research directions are examined. A marked increase in the number of publications has been observed since 2016, with a peak in 2018. In recent years, there has been a distinct trend toward the growth of comparative studies, making it possible to compare changes in the employment spheres of titular ethnic groups and other ethnonational communities in Russian regions. This is attributed to a general increase in research interest in the dynamics of ethnicity, global shifts in the domains of employment, and the development of scientific communication tools that stimulate publication activities on the subject. Most publications consist of journal articles and conference proceedings. Leading organizations in terms of publication output have been identified. Through comparative secondary analysis of the literature, both general and specific characteristics of the employment spheres of titular ethnic groups across various Russian regions have been revealed. All the examined ethnic groups are most widely represented in public service, science, and education sectors. The engagement of titular ethnic group members in certain spheres of employment is more closely tied to the existence of labor dynasties, kinship, and neighborhood ties than to intragroup network assistance based solely on ethnicity. The content of the reviewed works points to a diversity of both subjective and objective factors influencing individual career choices and collective labor behavior, which have contributed to the underrepresentation of most titular ethnic groups in industry and business. These factors include ethnocultural traditions, mentality, the persistence of labor dynasties, processes of modernization, industrialization, cultural revolution (expansion of mass education), and the Soviet-era policy of forming national elites from former lower social strata of the Russian Empire.